Interdependence of sentiment indicators − a case of the Polish OTC market - Jaworski, Piotr; Mielus, Piotr (Współzależność wskaźników sentymentu na przykładzie polskiego rynku pozagiełdowego, 2017)
Prices observed on emerging markets are affected by market sentiment changes. The article presents an interdependence analysis of a chosen set of sentiment indicators observed on the Polish OTC market. The set contains both interest rate market (basis swap, asset swap, convergence swap, overnight index swap), foreign exchange market (ATM volatility, risk reversal) and equity market (WIG20). The analysis is focused on cointegration and Granger causality approach in order to present forecasting power of elaborated models. Evidence from the market reveals economic link between the time series that comes from the strong influence of the cross-border trading between non-residents and local market makers. High responsiveness of daily prices of OTC instruments to the changes of the market sentiment and a level of the risk aversion can be proven. Moreover, error correction model using foreign exchange options has practical forecasting power generating adequate trading decisions taken by market makers
Nauki o Finansach = Financial Sciences, 2017, Nr 2 (31), s. 31-43
Keywords: emerging markets; market sentiment; cointegration analysis; rynki wschodzące; sentyment rynkowy; analiza kointegracji